Assessing local seismic response in major-hazard industrial plants: implications for natech events - Berardo, Giorgia; Giannini, Leonardo Maria; Marino, Alessandra; Maschio, Giuseppe; Mocellin, Paolo; Vianello, Chiara; Scarascia Mugnozza, Gabriele (Italian journal of engineering geology and environment, 2024)
Seismic events can trigger a NaTech disaster, leading to the release of hazardous materials, fires, and explosions. These can occur within industrial complexes and along distribution networks as a result of natural disasters. Industrial plants, composed of structural and non-structural components, may be damaged when subjected to earthquakes of a given magnitude. Some examples of these disasters occurred in Kobe (1995), Kocaeli (1999), and Tohoku (2011). This study aims to assess the local seismic hazard by the implementation of different analytical approaches in a Major-Hazard Industrial Plant (MHI P) triggering a NaTech event. For the Bussi MHI P area, a geodatabase has been designed where geometric and geotechnical parameters have been associated with each geotechnical unit. The local seismic hazard has been simulated using 1D and 2D codes, considering two seismic hazard scenarios limit state SLV - SLC according to the National Building Code (NTC2018). In this study, the amplification factor AF has been calculated within the natural vibration range of an H2O2 storage tank located in the Bussi MHI P facility. This type of structure was chosen as it represents an element able to generate a relevant accident and consequently, a potential NaTech event.